Inclusion Impact of Jack Mackerel Meal in the Red Sea Bream (Pagrus major) Feeds Replacing Various Animal Protein Sources for Fish Meal - Tae Woong Kwon; Seong Il Baek; Sung Hwoan Cho (Aquaculture Nutrition, 2024)
This study aims to elucidate manipulation impacts of jack mackerel meal (JMM) in the red sea bream (Pagrus major) feeds replacing various animal protein sources for different levels of fish meal (FM) on growth and feed availability. Two-way ANOVA experimental design was applied with three substitution sources: animal protein sources (tuna byproduct meal (TBM), chicken byproduct meal (CBM), and meat meal (MM)) and two FM substitution levels (25% and 50%). The control (Con) diet contained 60% FM. In the Con diet, 25% and 50% of FM were replaced with TBM, CBM, and MM, respectively, and then 24% jack mackerel meal (JMM) was included at the expense of FM, named as the TBM25, TBM50, CBM25, CBM50, MM25, and MM50 diets, respectively. Red sea bream juveniles averaging 11.8 g were distributed in 21 flow-through tanks (20 fish per tank) with triplicate. Fish were carefully hand-fed to apparent satiation for 8 weeks. At the end of the 8-week feeding experiment, the TBM-substituted diets produced significantly (P<0.0001 for all) greater weight gain, specific growth rate (SGR), and feed consumption of fish than the CBM- and MM-substituted diets. Furthermore, dietary substitution of 25% FM achieved significantly (P<0.0001, P<0.0001, and P<0.0003, respectively) greater weight gain, SGR, and feed consumption than dietary substitution of 50% FM based on two-way ANOVA analysis. Fish fed the TBM50 diet achieved the greatest weight gain, SGR, and feed consumption. Protein retention, biological indices, plasma and serum parameters, and the whole body chemical composition and amino acid (AA) profiles of red sea bream were not significantly influenced by dietary treatments. The TBM-substituted diets achieved significantly (P<0.0001) greater economic profit index (EPI) than the CBM- and MM-substituted diets. Furthermore, dietary substitution of 25% FM achieved significantly (P<0.002) greater EPI than dietary substitution of 50% FM. The TBM50 diet produced the greatest EPI. In conclusion, TBM and MM and CBM could replace 50% and 25% FM in the feeds with 24% JMM inclusion, respectively, without compromising the growth, feed utilization, plasma and serum parameters, chemical composition and AA profiles of red sea bream, and EPI. The TBM50 diet was the most desirable treatment in terms of the greatest growth performance of red sea bream and the highest economic return to farmer.